Laser beam oscillation strategy for weld geometry variation - Horník, Petr; Šebestová, Hana; Novotný, Jan; Mrňa, Libor (Journal of manufacturing processes, 2022)
This paper provides an insight into producing of laser welds with various cross-sections using beam oscillation techniques. Basic (line, circle, eight, and infinity) and advanced (celtic, flower, and atom) oscillation modes were experimentally investigated and compared to the conventional laser welds made with the same laser power and welding speed. Laser spot trajectories and time-dependent energy per unit spot trajectory length were visualized to explain the differences in weld cross-sections. The local power density distribution was calculated to estimate the weld geometry dependent on the oscillation mode, oscillation amplitude, frequency, and welding speed. [Display omitted]